Theatre Toronto Live, 1999: A Subjective Analysis of Theatre Life in Toronto1 - Szaffkó, Péter (FOCUS: Papers in English Literary and Cultural Studies, 2000)
Major theatres in London, Paris, Berlin, New York or those in Moscow, Prague, Cracow and Budapest are more or less well-known cultural institutions for people all over Europe. But can anyone not engaged in Canadian Studies name some important theatres or companies in Toronto or Montreal? Shakespeare scholars may be aware of the nearly four-decade-old Stratford Festival in Ontario and students of G. B. Shaw may know that a Shaw Festival has been operating successfully on the Niagara-on-the-Lake since 1962. But how much is known in Europe about such influential English-Canadian theatres as Theatre Passe Muraille, Tarragon, Factory, Buddies in Bad Times or the Canadian Stage Company? In his introduction to Contemporary Canadian Theatre: New World Visions, published in 1985, the editor Anton Wagner wrote the following: Enriched by multi-disciplinary experimentation, high artistic standards, coproductions, and increasing contact between various disciplines, the performing arts in Canada have reached a cultural critical momentum which augurs a new phase in Canada’s artistic history. Canada is poised on a phase of “cultural take-off’ in which regional artistic reflection and expression has attained national and international standards of significance. (19)